Intraoperative Navigation in Plastic Surgery with Augmented Reality: A Preclinical Validation Study. Issue 3 (March 2022) - Rudy, Hayeem L.; Schreiber, Jillian S.; Wake, Nicole; Lesko, Robert P.; Gordon, Alexandra; Garfein, Evan S.; Tepper, Oren M.
Abstract : Background: Augmented reality allows users to visualize and interact with digital images including three-dimensional holograms in the real world. This technology may have value intraoperatively by improving surgical decision-making and precision but relies on the ability to accurately align a hologram to a patient. This study aims to quantify the accuracy with which a hologram of soft tissue can be aligned to a patient and used to guide intervention. Methods: A mannequin's face was marked in a standardized fashion with 14 incision patterns in red and nine reference points in blue. A three-dimensional photograph was then taken, converted into a hologram, and uploaded to HoloLens (Verto Studio LLC, San Diego, Calif.), a wearable augmented reality device. The red markings were then erased, leaving only the blue points. The hologram was then viewed through the HoloLens in augmented reality and aligned onto the mannequin. The user then traced the overlaid red markings present on the hologram. Three-dimensional photographs of the newly marked mannequin were then taken and compared with the baseline three-dimensional photographs of the mannequin for accuracy of the red markings. This process was repeated for 15 trials ( n = 15). Results: The accuracy of the augmented reality-guided intervention, when considering all trials, was 1.35 ± 0.24 mm. Markings that were positioned laterally on the face were significantly more difficult to reproduce than those centered around the facial midline. Conclusions: Holographic markings can be accurately translated onto a mannequin with an average error of less than 1.4 mm. These data support the notion that augmented reality navigation may be practical and reliable for clinical integration in plastic surgery.